Organ-specific Microplastic Accumulation and Associated Oxidative Stress and Immune Responses in Barbonymus gonionotus from Downstream Bengawan Solo River, Indonesia - Ma'rufah, Asmaul Lutfi; Setiyowati, Putri Ayu Ika; Ramadani, Aisyah Hadi; Bukhori, Fika Nur Fitriana Putri; Iqbal, Muhammad (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. Comperhensive assessment of microplastic accumulation and oxidative stress-mediated immune responses in Barbonymus gonionotus from the Bengawan Solo River. 2. Gills showed the highest microplastic loads, with evidence of systemic translocation to muscle tissue. 3. Elevated leukocyte counts, MDA, and TNF-α indicate immune activation and oxidative stress from microplastic. 4. Combining particle characteristics with biological endpoints provides a sensitive biomonitoring framework.   Abstract Microplastics (MPs) contamination is an emerging threat in freshwater ecosystems; however, field-basesd evidence of organ-specific accumulation and physiological stress in wild Barbonymus gonionotus remains limited. This study investigated MPs accumulation, oxidative stress, and immune responses in B. gonionotus collected from three downstream sites (BD, DD, UPD) of the Bengawan Solo River, East Java, Indonesia (July–August 2024). Thirty adult fish (n = 10 per site) were analyzed for MPs in gill, intestine, and muscle tissues using KOH digestion, visual classification of particle type, color, and size, and hot-needle testing, without chemical polymer confirmation. Total leukocyte counts, TNF-α, and MDA were measured to assess immune and oxidative stress responses. MPs were most abundant in gills and surface water, dominated by fragments and pellets sized 100–300 µm, with black and brown particles prevailing. The highest MPs concentrations in water and fish tissues were observed at UPD, where muscle tissues also showed MPs accumulation, suggesting systemic translocation of smaller particles. Fish from this site exhibited elevated leukocyte counts, increased TNF-α, and higher MDA levels, reflecting immune activation and oxidative stress associated with MPs exposure. These findings indicate chronic MPs exposure in downstream fish populations, evidenced by hematological and oxidative responses. Integrating organ-specific MPs assessment with leukocyte, TNF-α, and MDA profiling provides a sensitive biomonitoring approach for tropical freshwater ecosystems.